2001
DOI: 10.1159/000046708
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Distribution and Total Body Fat as Risk Factors for Microalbuminuria in the Obese

Abstract: Background/Aim: Despite evidence linking type of obesity with subsequent organ malfunction, such a link with renal malfunction has not been widely researched. The aim of this study was to investigate percentage of total body fat (%TBF), and body fat distribution in relation to the renal function in overweight/obese subjects. Methods: Body mass index (BMI), waist-to-hip ratio (WHR), TBF (by bioelectric impedance), and albumin excretion rate (AER) were determined in 77 subjects: 48 overweight/obese (BMI ≧27.8 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 20 publications
1
33
0
2
Order By: Relevance
“…When hypertension was associated with obesity, the prevalence reached up to 19% 18 . In another study with obese or overweight individuals, central fat distribution implied an 18-fold higher risk of microalbuminuria in relation to lean individual, whereas among obese individuals with peripheral fat distribution, the risk was 4-fold higher 19 . A Brazilian study demonstrated a trend to borderline levels of nocturnal microalbuminuria, which was higher in normotensive obese females with central fat distribution 20 .…”
Section: Discussionmentioning
confidence: 89%
“…When hypertension was associated with obesity, the prevalence reached up to 19% 18 . In another study with obese or overweight individuals, central fat distribution implied an 18-fold higher risk of microalbuminuria in relation to lean individual, whereas among obese individuals with peripheral fat distribution, the risk was 4-fold higher 19 . A Brazilian study demonstrated a trend to borderline levels of nocturnal microalbuminuria, which was higher in normotensive obese females with central fat distribution 20 .…”
Section: Discussionmentioning
confidence: 89%
“…The consequence of abdominal adiposity in relation to kidney function impairment has been little documented and it is a noteworthy subject, considering its frequent association with hypertension and diabetes, which are the main causes of CKD in the world. Some studies have shown an association between the central distribution of fat, measured by the WHR, with hypertension 14,27 , microalbuminuria 28 and CKD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…BMI and %TBF were highly correlated (r 2 ¼0.5 for men, and r 2 ¼0.45 for women). Since no national figures are available for % TBF in Australia, the mean % TBF of this group was compared to that of a group of Caucasians of similar age and BMI (determined in our laboratory using the same methodology (Mulyadi et al, 2001). The mean values of % TBF for this group was 18.0 for men and 31.8 for women.…”
Section: Indian Resident Groupmentioning
confidence: 99%